2021
DOI: 10.3390/nu13113958
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of TRX Suspension Training Combined with Taurine Supplementation on Body Composition, Glycemic and Lipid Markers in Women with Type 2 Diabetes

Abstract: Background: We aimed to investigate the effects of an 8-week total-body resistance exercise (TRX) suspension training intervention combined with taurine supplementation on body composition, blood glucose, and lipid markers in T2D females. Methods: Forty T2D middle-aged females (age: 53 ± 5 years, body mass = 84.3 ± 5.1 kg) were randomly assigned to four groups, TRX suspension training + placebo (TP; n = 10), TRX suspension training + taurine supplementation (TT; n = 10), taurine supplementation (T; n = 10), or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 62 publications
3
18
0
Order By: Relevance
“…The literature search identified 2206 studies, of which 471 studies were from PubMed, 37 were from the Cochrane Library, 902 were from Embase, 790 were from the Web of Science and 6 were from clinical trials. After excluding 563 duplicates, reviewing 1643 titles and abstracts, 1557 outcomes were excluded, and the remaining 86 outcomes were sought for retrival, The full text of 10 articles can not be obtained, 54 articles were assessed in detain, of which 28 studies were excluded for interventions not eligible, 16 studies were excluded for patients not eligible, 10 studies were excluded for outcomes not eligible, resulting in a total of 5 randomized controlled studies of taurine for diabetes included in the meta-analysis ( Esmaeili et al, 2021 , Moloney et al, 2010 , Premanath et al, 2019 , Samadpour Masouleh et al, 2021 , Svarovskaya and Garganeeva, 2018 ). The study selection process is summarized in the PRISMA flow chart ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The literature search identified 2206 studies, of which 471 studies were from PubMed, 37 were from the Cochrane Library, 902 were from Embase, 790 were from the Web of Science and 6 were from clinical trials. After excluding 563 duplicates, reviewing 1643 titles and abstracts, 1557 outcomes were excluded, and the remaining 86 outcomes were sought for retrival, The full text of 10 articles can not be obtained, 54 articles were assessed in detain, of which 28 studies were excluded for interventions not eligible, 16 studies were excluded for patients not eligible, 10 studies were excluded for outcomes not eligible, resulting in a total of 5 randomized controlled studies of taurine for diabetes included in the meta-analysis ( Esmaeili et al, 2021 , Moloney et al, 2010 , Premanath et al, 2019 , Samadpour Masouleh et al, 2021 , Svarovskaya and Garganeeva, 2018 ). The study selection process is summarized in the PRISMA flow chart ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…After excluding this group of data, the heterogeneity was reduced to zero, so this group of data was not included. A total of five RCTs ( Esmaeili et al, 2021 , Moloney et al, 2010 , Premanath et al, 2019 , Samadpour Masouleh et al, 2021 , Svarovskaya and Garganeeva, 2018 ), reported, in a total of 199 patients, 113 taurine users and 86 non-users, that taurine had the potential to reduce TG compared to controls (SMD −0.26 [95% CI: −0.55, 0.02], p = 0.07), but the difference was not statistically significant. There was no heterogeneity between studies (p = 0.43, I 2 = 0%) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations